NEW PATIENT ADMISSION MODEL BASED ON INTERPERSONAL RELATIONSHIPS AND ITS IMPACT ON NURSE PERFORMANCE IN HOSPITALS: A SYSTEMATIC - Novia Caecilia Laoli; Nursalam; Ilya Krisnana (Nurse and Holistic Care, 2026)
Background: The admission of new patients is a critical phase in inpatient care that shapes first impressions, emotional responses, and perceptions of healthcare quality. Nurses play a central role in this process, where strong interpersonal competence is essential. Interpersonal relationship–based admission models are proposed to improve nurse performance and patient experience, although supporting evidence remains fragmented. Objective: To evaluate impact of interpersonal relationship based new patient admission models on nurse performance. Methods: This systematic review accordance with PRISMA guidelines. Studies were selected using the PICOS framework. Cross-sectional and quasi-experimental studies examining interpersonal relationship based new patient admission models and their impact on nurse performance were included. Risk of bias was assessed using JBI Critical Appraisal Checklist. Data were synthesized narratively. Results: From 5,033 records, ten studies met inclusion criteria after duplicate removal, two-stage screening, and consensus-based selection. Eligible open-access studies underwent standardized extraction of study characteristics, interventions, and nurse performance outcomes, and selection was reported via the PRISMA flow diagram. The included studies show that interpersonal relationship–based admission approaches such as therapeutic communication, structured patient orientation, and digital or educational media improve nurse performance. Key outcomes include enhanced communication effectiveness, adherence to procedures, patient adaptation, and satisfaction. Conclusion: Interpersonal relationship–based approaches applied in admission-related nursing processes particularly therapeutic communication and patient orientation are associated with improved nurse performance and patient outcomes. However, further rigorous studies focusing specifically on new patient admission are needed to strengthen the evidence.